Productivity and growth in Singapore : the role of TFP growth measurement in public policy debate - Lall, Ashish (2008)
This report analyzes total factor productivity performance in Singapore by looking at the influence of dynamic factors captured by changes in the rates of capacity utilization in the manufacturing sector.